Prospective Evaluation of the Radiologist’s Hand Dose in CT-Guided Interventions - Rogits, B.; Jungnickel, K.; Löwenthal, D.; Kropf, S.; Nekolla, E. A.; Dudeck, O.; Pech, M.; Wieners, G.; Ricke, J. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: Assessment of radiologist’s hand dose in CT-guided interventions and determination of influencing factors. Materials and Methods: The following CT-guided interventions were included: Core biopsy, drainage, periradicular therapy, and celiac plexus neurolysis. The hand dose was measured with an immediately readable dosimeter, the EDD-30 (Unfors, Sweden). The default parameters for CT fluoroscopy were 120 kV, 90 mA and a 4 mm slice thickness. All interventions were performed on a 16-slice CT unit (Aquilion 16 Toshiba, Japan). The tumor size, degree of difficulty (1 – 3), level of experience and device parameters (mAs, dose-length product, scan time) were documented. Results: 138 CT-guided interventions (biopsy n = 99, drainage n = 23, pain therapy n = 16) at different locations (lung n = 41, retroperitoneum n = 53, liver n = 25, spine n = 19) were included. The lesion size was 4 – 240 mm (median: 23 mm). The fluoroscopy time per intervention was 4.6 – 140.2 s (median: 24.2 s). The measured hand dose ranged from 0.001 – 3.02 mSv (median: 0.22 mSv). The median hand dose for lung puncture (n = 41) was slightly higher (median: 0.32 mSv, p = 0.01) compared to that for the liver, retroperitoneum and other. Besides physical influencing factors, the degree of difficulty (p = 0.001) and summed puncture depth (p = 0.004) correlated significantly with the hand dose. Conclusion: The median hand dose for different CT-guided interventions was 0.22 mSv. Therefore, the annual hand dose limit would normally only be reached with about 2000 interventions.Key Points:Citation Format:
Keywords: radiation effects; radiation safety; CT fluoroscopy; biopsy; interventional procedures